A regression discontinuity evaluation of reducing early retirement eligibility in Poland - Oliwia Komada; Pawel Strzelecki; Joanna Tyrowicz (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2018)
The reform introduced in Poland in 2009 substantially and abruptly reduced the number of workers eligible for early retirement. This paper evaluates the causal effects of this reform on labor force participation and exit to retirement. We use rich rotating panel from the Polish Labor Force Survey and exploit the discontinuity imposed by this reform. We find a statistically significant, but economically small discontinuity at the timing of the reform. The placebo test shows no similar effects in earlier or later quarters, but in a vast majority of specifications the discontinuity is not larger for the treated individuals, i.e. those whose occupation lost eligibility. We interpret these results as follows: the changes in the eligibility criteria were not instrumental in fostering the participation rates among the affected cohort, i.e. the immediate contribution to increased labor force participation of these cohorts is not economically large.
Keywords: J14; J26; 330; retirement age; early retirement; regression discontinuity; Poland